UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING PADA SISWA KELAS VII B SMPN 3 DUSUN SELATAN KABUPATEN BARITO SELATAN - Subiyanto, Hendro (Nusantara Hasana Berdikari, 2022)
This research aims to describe the use of Quantum Teaching in improving the learning outcomes of students of class VII B SMPN 3 South Hamlet in IPS learning. The study subjects were students of class VII B SMPN 3 as many as 26 people, consisting of 13 men and 13 women. The implementation of this research in the first semester of the 2021/2022 school year, which is September to November 2021. Learning value data is obtained by conducting tests of learning results, with written test questions in the form of descriptions. Data on student learning outcomes are analyzed based on the requirements of learning completion, namely by comparing the value obtained by students with the Minimum Completion Criteria (KKM). The results showed a significant improvement in the value of students' learning outcomes. The improvement in student learning outcomes is evidenced by an increase in the value of student learning outcomes in each cycle. The increase in the number of students who gained grades more than or equal to 68 or can reach KKM also increased, namely as many as 14 (53.85%) students in presiclus, increased to 19 (73.08%) students in cycle I, and increased again to 23 (88.46%) in cycle II. The results of this study showed that after the last cycle of learning outcomes students have achieved the completion of classical learning. Penelitian ini bertujuan untuk mendeskripsikan penggunaan Quantum Teaching dalam meningkatkan hasil belajar siswa kelas VII B SMPN 3 Dusun Selatan dalam pembelajaran IPS. Subjek penelitian adalah siswa kelas VII B SMPN 3 sebanyak 26 orang, terdiri dari 13 laki-laki dan 13 perempuan. Pelaksanaan penelitian ini pada semester I tahun pelajaran 2021/2022, yaitu bulan September sampai November 2021. Data nilai hasil belajar diperoleh dengan melakukan tes hasil belajar, dengan soal tes tertulis berbentuk uraian. Data hasil hasil belajar siswa dianalisis berdasarkan ketentuan ketuntasan belajar, yaitu dengan membandingkan nilai yang diperoleh siswa dengan Kriteria Ketuntasan Minimal (KKM). Hasil penelitian menunjukkan terjadinya peningkatan yang signifikan pada nilai hasil belajar siswa. Peningkatan hasil belajar siswa dibuktikan dengan terjadinya peningkatan nilai hasil belajar siswa pada tiap-tiap siklus. Peningkatan jumlah siswa yang memperoleh nilai lebih dari atau sama dengan 68 atau dapat mencapai KKM juga mengalami peningkatan, yaitu sebanyak 14 (53,85%) siswa pada prasiklus, meningkat menjadi 19 (73,08%) siswa pada siklus I, dan meningkat lagi menjadi 23 (88,46%) pada siklus II. Hasil penelitian ini menunjukkan bahwa setelah siklus terakhir hasil belajar siswa telah mencapai ketuntasan belajar secara klasikal.